2002
DOI: 10.1016/s0014-5793(02)02301-3
|View full text |Cite
|
Sign up to set email alerts
|

Tandem termination signals: myth or reality?

Abstract: In two Escherichia coli genomes, laboratory strain K-12 and pathological strain O157 :H7, tandem termination codons as a group are slightly over-represented as termination signals. Individually however, they span the range of representations, over, as expected, or under, in one or both of the strains. In vivo, tandem termination codons do not make more efficient signals. The second codon can act as a backstop where readthrough of the first has occurred, but not at the expected efficiency. UGAUGA remains an eni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…It is interesting to note that TAG is also significantly underrepresented as the tandem stop codon when TAA and TGA are the primary stop codons (15) (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that TAG is also significantly underrepresented as the tandem stop codon when TAA and TGA are the primary stop codons (15) (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in E. coli ϳ7% of all genes possess an additional stop codon where a second stop codon is present immediately downstream of the primary stop codon (15). Because TAG is the minor stop codon, we wanted to check whether there is any bias for an additional stop codon for the genes ending with TAG.…”
Section: Distribution Of Stop Codons Within and Across Different Bac-mentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrate that a single stop codon is sufficient to terminate trans-translation in vivo, even under experimental conditions where numerous truncated L27 mRNA molecules are engaged with translation-arrested ribosomes. Why the tmRNAs of several bacterial species contain clusters of tandem stop codons within the terminal loop of helix 5 remains to be determined (Zwieb et al 1999a,b; see also Major et al 2002); however, one can speculate that their function comes into play when cells are exposed to stress. Interestingly, the context in which tandem stop codons were placed (nonaloop vs. tetraloop) did not affect tagging efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true in the case of UGAN and UAAN signals utilized by highly expressed genes, where in the +4 position (N), pyrimidine is preferred to purine, with uridine usually the strongest. The presence of tandem stop codons, UGAUGA for example, was thought to be advantageous, since it appeared to be over-represented in the genomes of bacteria, however, from analysis using the reporter systems, it seems that tandem stop signals confer no additional advantage other than having the +4 position uridine [49]. Further support for a direct interaction between RFs and the extended termination signal came when crosslinks from the +4 position [50] and weaker crosslinks from the +5 and +6 positions (but not +7 to +10 positions) [48] with the RF were demonstrated.…”
Section: Codon Recognition Domain Of Bacterial Rfs: the Termination Smentioning
confidence: 99%